The TP* Conveyor - Landolfi, Angela; Koeve, Wolfgang; Dietze, Heiner; Oschlies, Andreas (2012)
Given the elevated energetic costs of biological N2 fixation, marine diazotrophs may out-compete non-fixing phytoplankton only in N poor regions. This paradigm is apparently in contrast with the observation of high N2 fixation rates in the subtropical North Atlantic where vertical nutrient fluxes to the euphotic zone are high in nitrate relative to phosphate, exceeding the needs of non-fixing phytoplankton. A mechanism potentially resolving this apparent paradox is the transport of accumulated excess inorganic (PO4) and organic (DOP) phosphorus, TP*, from distant regions of its formation to the North Atlantic subtropical gyre. In this contribution we explore the sensitivity of TP* accumulation to environmental factors and the potential TP* transport pathways using a state - of - the - art global coupled biogeochemical ocean model. Understanding the controls on marine N2 fixation is of fundamental importance to interpret past and predict future changes of the marine N inventory.